CdTe surface passivation by electric field induced at the metal-oxide/CdTe interface. (1st September 2021) - Wu, Lingling; Li, Zihan; Wang, Dongming; Lei, Xunyong; Cai, Yanbo; Zeng, Hualing; Zhu, Peng; Wang, Deliang
Highlights: The CdTe surface was passivated by the sputtered Al2 O3 and V2 O5 layers. The minority carrier lifetime of the CdTe covered with Al2 O3 and V2 O5 was increased. There exsits negative fixed charges in V2 O5 and Al2 O3 . The passivation was ascribed to the electric field effect. Abstract: In this study, three kinds of metal oxide (MOs), namely, V2 O5, Al2 O3 and NiO, were deposited on CdTe thin films to study possible passivation effect on the CdTe surface. Time-resolved photoluminescence (TRPL) measurements were carried out to study the minority carrier lifetime of the MO-coated CdTe and bare CdTe. The results showed that the TRPL decay curves were consisted of a fast and a slow decay process for all samples. For both the bare and NiO-coated CdTe surface, the fast and the slow decay lifetimes were found to be 0.5 and 1.0 ns. While for the Al2 O3 - and V2 O5 -coated CdTe, the fast decay lifetime was 0.6 and 0.7 ns, and the slow decay lifetime was 2.1 and 2.4 ns, respectively. CdTe surface defect states with high surface recombination velocity, 10 6 cm/s, were responsible for the fast decay. The CdTe surface was effectively passivated by a 3-nm-thick V2 O5 or Al2 O3 coating layer. The simulation and experimental results indicated that the passivation was ascribed to the electric field effect induced by negative fixed charges in V2 O5 and Al2 O3 .